Burden of rheumatoid arthritis among US Medicare population: co-morbidities, health-care resource utilization and costs. Issue 1 (21st February 2018) - Chen, Chieh-I; Wang, Li; Wei, Wenhui; Yuce, Huseyin; Phillips, Kristine
Abstract: Objectives: The study aimed to assess the burden of RA among the US Medicare population (aged ≥65 years) by comparing co-morbidities, health-care resource utilization (HCRU) and costs against matched non-RA Medicare patients. Methods: Data were obtained from the Medicare fee-for-service claims database from 2010 to 2013. RA Medicare patients were identically matched with Medicare patients without RA (controls) based on demographics. Bivariate analyses were conducted to examine differences between cohorts for co-morbidities, HCRU and costs. A generalized linear model was used to test relationships between patient-level characteristics, HCRU and costs. Results: The study population included 115 867 RA patients and 115 867 age-, sex-, race- and region-matched non-RA controls. Mean age was 75.2 years; 79.4% were female. Co-morbidities were greater in RA vs non-RA patients [Charlson Co-morbidity Index (excluding RA): 1.86 vs 1.00; P < 0.0001]. All-cause annual HCRU was greater in RA vs non-RA patients. Total annual health-care costs were ∼3-fold higher in RA vs non-RA patients (20 919 vs 7197, respectively; P < 0.0001) with the major driver of costs in the RA cohort being outpatient costs. Approximately half of the overall costs in the RA cohort were RA related (11 587). After controlling for differences in patient characteristics and co-morbidities between cohorts, the adjusted total mean annual costs for RA patients were still more than twice those of non-RA patients (16 374 vs 6712; P < 0.0001). Conclusions: Among US Medicare patients, those with an RA diagnosis had a significantly greater burden of co-morbidities, HCRU and costs compared with a matched cohort without RA.